2019
DOI: 10.1007/s00125-019-05025-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cathepsin D activity is negatively associated with hepatic insulin sensitivity in overweight and obese humans

Abstract: Aims/hypothesis Insulin resistance in skeletal muscle and liver plays a major role in the pathophysiology of type 2 diabetes. The hyperinsulinaemic-euglycaemic clamp is considered the gold standard for assessing peripheral and hepatic insulin sensitivity, yet it is a costly and labour-intensive procedure. Therefore, easy-to-measure, cost-effective approaches to determine insulin sensitivity are needed to enable organ-specific interventions. Recently, evidence emerged that plasma cathepsin D (CTSD) is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
3
13
0
Order By: Relevance
“…Our data therefore point toward plasma CTSD as a novel metabolic regulator in type 2 diabetes. These findings are in line with our previous studies that demonstrated a role for plasma CTSD activity in lipid metabolism and insulin resistance ( 18 , 23 , 24 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data therefore point toward plasma CTSD as a novel metabolic regulator in type 2 diabetes. These findings are in line with our previous studies that demonstrated a role for plasma CTSD activity in lipid metabolism and insulin resistance ( 18 , 23 , 24 ).…”
Section: Discussionsupporting
confidence: 93%
“…diabetes (24). More specifically, increasing reports link CTSD activity to disturbances in lipid metabolism (18,23), a finding which we could also confirm in here in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, in rodent models it has been reported that whole-body pharmacological and genetic inactivation of CTSB protected against the development of hepatic steatosis and whole-body insulin resistance [ 24 ]. We previously observed in a sub-study of this cohort that plasma Cathepsin D (CTSD) activity, but not systemic inflammation, is inversely related to hepatic insulin sensitivity, suggesting that plasma CTSD activity may be used as a non-invasive marker for hepatic insulin sensitivity in humans [ 25 ]. The observed fasting lysosomal dysfunction might compromise the ability of the cell to perform quality control on the mitochondrial matrix, since autophagy plays a pivotal role in the degradation of defective mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, plasma cathepsin D levels associated with metabolic alterations in liver during NAFLD [ 187 ]. Recent studies suggested that plasma cathepsin D levels correlated with type 2 diabetic patients [ 188 ] and moreover plasma cathepsin D activity is suggested as biomarker for hepatic insulin sensitivity [ 189 ]. Cathepsins Z and K are proposed diagnostic markers for osteoporosis [ 190 , 191 ].…”
Section: Targeting Cathepsins In Disease Managementmentioning
confidence: 99%